Superionic behavior in the xAgI–(1−x)CsAg2I3 polycrystalline system. (June 2016) - Rodríguez, L.A.; Zapata, J.; Vargas, R.A.; Peña Lara, D.; Diosa, J.E.
Abstract: A superionic phase behavior (with DC ionic conductivities higher than 0.01 S/cm) has been observed in x AgI–(1− x )CsAg2 I3 ( x ≈0.67) polycrystalline system grown by slow evaporation using AgI and CsI powders (molar ratio Cs/Ag=0.25) as starting salts and an aqueous solution of HI as solvent. The transition from the normal-to- the superionic state is first-order with a hysteretic behavior in temperature centered at about 116 °C as reflected by thermal (DSC) and electrical conductivity measurements. This mixture is composed of CsAg2 I3 and AgI crystalline phases and an additional amorphous AgI phase that explains the glassy-type behavior observed in the superionic phase transition. Highlights: The CsAg2 I3 –AgI binary system shows a superionic state and high-temperature phase transitions. The ionic conductivity in the superionic state is 10 −2 S/cm and activation energy 0.24 eV. The electrical properties of CsAg2 I3 –AgI are interesting for applications in electrochemical devices.